Analysis of the rhetorical and linguistic concept of the two linguistic signs "Mohtasb" and "Donya" in a lyric by Hafez Based on Omberto Eco's semiotic approach - Yahya Nooraddini Agdam; Narges Mohammadi Badr; Gholamreza Ghaybi (مطالعات زبانی و بلاغی)
Most of the Hafez’s poems are rhetorical criteria that appear in the field of "language" and "meaning," and lead to the perception of the audience to layers beyond the initial level of expression. Hafez provides a complex process for expressing his artistic expressions that we can now explain in terms of semiotics. To explain this, the specific views of Umberto Eco in semiotics are very important. The adaptation of his view on Hafez's poems can provide significant theoretical bases for the semiotics of Hafez's poetry; In Eco's view, "role of the sign" has an implicit concept and acts as a link between the form of expression and the form of content. This concept can, in general, also be a kind of linguistic rhetoric; In the present article, an attempt is made to study the two signs of "Mohtaseb" and "the world" in a descriptive analytical research in one of the famous sonnets of Hafez based on the echo denominational approach. The research results indicate that Hafez uses concrete signs in his literary and contemporary atmosphere to express his poetry's thoughts and realms; his use of these signs is not limited to the exterior level of the language, but he tries to do so by the means that we can use it. Consider the functions of a sign to create a much wider scope and find a multi-dimensional area that is worthy of attention in both rhetoric and meaning.